Green Accounting Strategies in Sustainable Finance: : A Case Study of Cocoa Business Actors in West Sulawesi - Novitasari, Eni; M, Nuraeni; Hijrah, Muh; Erwin (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to develop and apply a Sustainability Balanced Scorecard (SBSC) model as a tool for measuring and evaluating sustainability performance in the cocoa industry of West Sulawesi. The urgency of this research is driven by the significant challenges confronting the cocoa industry, including social (labor exploitation), environmental (deforestation), and economic (supply chain opacity) issues, coupled with the absence of a structured accountability mechanism to objectively measure sustainability strategies. This study employs a mixed-method approach with a case study strategy on two companies representing the industry spectrum: a mission-driven Micro, Small, and Medium Enterprise (MSME) and a compliance-driven B2B exporter. Primary data were collected through in-depth interviews, while secondary data were analyzed from company financial reports. The findings reveal that company performance measurement can be centered on an Adaptive SBSC framework that integrates five perspectives: Financial, Customer, Internal Business Process, Learning and Growth, and a combined Environmental and Social perspective. This framework offers a two-tier indicator system (Basic and Advanced Performance Measurement) applicable to companies of varying scales and business models, serving as a flexible strategic management tool. This model contributes practically to actors in the cocoa industry and theoretically enriches the SBSC literature within the agro-industrial context of developing regions.